2021
DOI: 10.3390/vaccines10010031
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pediatric Vaccine Hesitancy among Racially Diverse Parents in the United States

Abstract: On 29 October 2021, the U.S. FDA authorized the Pfizer-BioNTech COVID-19 (SARS-CoV-2) vaccine for emergency use in children ages 5–11 years. Racial/ethnic minorities have born the greatest burden of pediatric COVID-19 infection and hospitalization. Research indicates high prevalence of parental vaccine hesitancy among the general population, underscoring the urgency of understanding how race/ethnicity may influence parents’ decision to vaccinate their children. Two weeks prior to FDA approval, 400 Hispanic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
85
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(96 citation statements)
references
References 39 publications
9
85
2
Order By: Relevance
“…Among parents who themselves were vaccinated, the unadjusted odds of vaccine uptake for their older child were 14 times higher than unvaccinated parents. Our findings are consistent with previous research reporting that vaccinated parents are more likely than unvaccinated parents to accept the vaccine for their children ( 6 , 8 – 10 , 12 , 16 , 17 , 19 , 21 , 22 ). Further, our data point to the influence of one's larger social context on vaccine acceptance.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Among parents who themselves were vaccinated, the unadjusted odds of vaccine uptake for their older child were 14 times higher than unvaccinated parents. Our findings are consistent with previous research reporting that vaccinated parents are more likely than unvaccinated parents to accept the vaccine for their children ( 6 , 8 – 10 , 12 , 16 , 17 , 19 , 21 , 22 ). Further, our data point to the influence of one's larger social context on vaccine acceptance.…”
Section: Discussionsupporting
confidence: 93%
“…Among our sample, parental COVID-19 misconceptions, general vaccine mistrust, and COVID-19 individualist attitudes were found to decrease the odds of vaccine uptake whereas COVID-19 safety measures and collectivist attitudes improved the odds of vaccine uptake. Previous research has found that parents' misconceptions about COVID-19 transmission, symptoms, and severity, and their general attitudes about pediatric vaccine safety are significant barriers to vaccine acceptance ( 6 , 8 – 11 , 13 21 ). Consequently, future research must identify public health measures that are effective in reducing vaccine misconceptions and mistrust while also being sensitive to differences in the influence of these concerns across different racial/ethnic groups of parents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The factor most strongly associated with vaccination intention for children was parental vaccination status. Recent studies examining COVID-19 vaccination intention, 17,18 including a recent international meta-analysis, 19 also have found that parents vaccinated against COVID-19 are much more likely to have their children vaccinated as well. Studies indicate that parents who are vaccinated against COVID-19 are also more likely to be vaccinated against influenza 20 and give greater weight to physician recommendations.…”
Section: Figure 3: Factors Informing Parent's Decision To Have Their ...mentioning
confidence: 99%
“…Studies indicate that parents who are vaccinated against COVID-19 are also more likely to be vaccinated against influenza 20 and give greater weight to physician recommendations. 17 Certain demographic and socioeconomic factors were associated with intention to vaccinate. Our finding that younger parents were more likely to be undecided or without intention to vaccinate is consistent with other studies as well.…”
Section: Figure 3: Factors Informing Parent's Decision To Have Their ...mentioning
confidence: 99%